Microscopy for pH mapping in nanofluidic devices - Enevold, Victor (My University, 2025)
Nanotechnology, along with related fields such as nanofluidics, is an area of science with much potential. Research into material properties at the nano-scale is driving innovation across various fields, such as the development of new drugs in medicine, and improve ments to solar cells in the development of sustainable energy. This thesis examines the possibility of creating and measuring pH gradients in nanofluidic channels, as a novel method to study nanoparticles subjected to different pH environments. The presented process relies on fluorescence microscopy and a pair of double Amici prisms. When ob serving fluorescent particles or dyes in the nanochannels, the fluorescence is angularly dispersed by the prisms. This enables measurements that capture spatial distribution of particles along the nanochannels, and corresponding spectral information dispersed per pendicularly. The experiments confirm that it is possible to generate a pH gradient in the nanochannels, as well as to move it by applying pressure to the ends on the chan nels. The presented results are largely based on the use of the pH-sensitive fluorescent dye SNARF-1, and a foundation for future study with nanoparticle FRET probes is also provided.
Keywords: Nanofluidics, Fluorescence, Microscopy, Amici prism, SNARF-1, pH gradi ent